Defining an adequate sample of earlywood vessels for retrospective injury detection in diffuse-porous species. - Estelle Arbellay (Public Library of Science (PLoS), 2012)
Vessels of broad-leaved trees have been analyzed to study how trees deal with various environmental factors. Cambial injury, in particular, has been reported to induce the formation of narrower conduits. Yet, little or no effort has been devoted to the elaboration of vessel sampling strategies for retrospective injury detection based on vessel lumen size reduction. To fill this methodological gap, four wounded individuals each of grey alder (Alnus incana (L.) Moench) and downy birch (Betula pubescens Ehrh.) were harvested in an avalanche path. Earlywood vessel lumina were measured and compared for each tree between the injury ring built during the growing season following wounding and the control ring laid down the previous year. Measurements were performed along a 10 mm wide radial strip, located directly next to the injury. Specifically, this study aimed at (i) investigating the intra-annual duration and local extension of vessel narrowing close to the wound margin and (ii) identifying an adequate sample of earlywood vessels (number and intra-ring location of cells) attesting to cambial injury. Based on the results of this study, we recommend analyzing at least 30 vessels in each ring. Within the 10 mm wide segment of the injury ring, wound-induced reduction in vessel lumen size did not fade with increasing radial and tangential distances, but we nevertheless advise favoring early earlywood vessels located closest to the injury. These findings, derived from two species widespread across subarctic, mountainous, and temperate regions, will assist retrospective injury detection in Alnus, Betula, and other diffuse-porous species as well as future related research on hydraulic implications after wounding.